Love waves in layered flexoelectric structures. Issue 33 (22nd November 2017) - Yang, Wenjun; Liang, Xu; Shen, Shengping
Abstract: In this paper, the flexoelectric effect on Love waves propagating in a structure with a nanoscale piezoelectric guiding layer deposited on an isotropic elastic substrate is analytically investigated. Transcendental complex dispersion equations are obtained and solved numerically which are corresponding to the electrically open and short conditions at the free surface. A detailed discussion about the dispersion relations of the fundamental mode is subsequently presented. The results indicate that flexoelectricity has a substantial effect on Love wave propagation. The presence of flexoelectricity leads to a complex phase velocity with a negative/positive imaginary part, which means Love waves attenuate/grow over time. In addition, the phase velocity dispersion relations depend greatly on the thickness and flexoelectric coefficients of the guiding layer. The current work is the first attempt to explore the flexoelectric effect on the propagation characteristics of surface acoustic waves (SAWs). And the results would be beneficial to achieve a better performance of SAW devices.